Ask a Question

3(2x-4)=7x-8

+3 votes
asked Oct 18, 2013 in Algebra by anonymous
   

1 Answer

0 votes
3(2x - 4) = 7x - 8 (multiply the 3 into the parenthesis to get the following)

6x - 12 = 7x - 8 (add 8 to both sides of the equation)

6x - 4 = 7x (subtract 6x from both sides of the equation)

-4 = x
answered Oct 19, 2013 by stg1.stewart Inquisitive Expert (21,460 points)

Categories

ExplainPlease on Facebook

75,014 questions

48,874 answers

1,169 comments

83,334 users

CuriousGirl313,480
BobTheAnswerGuy310,070
smartguy111,120
charlie100,740
bbrown97,580
answerwiz94,860
The.Sage93,460
amanda0192,460
kfox83,500
lsmith82,840
...